Optimalisasi Peran Generasi Z sebagai Khatib Muda dalam Membangun Peradaban Umat di Era Digital - Ma’zumi, Ma’zumi; Suja’i, Suja’i; Najmudin, Najmudin (Forum Kerjasama Pendidikan Tinggi, 2026)
The Friday sermon (khutbah Jum‘ah) faces challenges in engaging Generation Z, as sermons often seem detached from their realities. Yet, the khutbah has strategic potential as a tool for spiritual and social development within the mosque community. This community service program aims to strengthen the capacity of young preachers (khatib muda) from Generation Z through contextual sermon training that is relevant to the challenges of the digital era, while utilizing the mosque as a center for community empowerment. The program was carried out in collaboration with the Campus Mosque of Sultan Ageng Tirtayasa University, a strategic partner that provided participants, facilities, and support for implementing post-sermon action programs. The project used a Participatory Action Research (PAR) approach, emphasizing that participants actively engaged in every program stage, including: (1) intensive training for young preachers on sermon substance and the mosque’s social role; (2) sermon practice and direct mentoring; (3) observing and evaluating sermon delivery; and (4) conducting post-sermon social and religious action programs. Data were collected through participatory observation, interviews, and documentation, and analyzed descriptively and qualitatively using triangulation techniques. The activities showed a significant improvement in participants’ rhetorical competence, sermon content, and social sensitivity. Approximately 85% of participants successfully developed sermon manuscripts with contextual themes, and 78% delivered sermons that engaged the audience. Post-sermon programs such as Green Dakwah, Masjid Talk Gen Z, and digital literacy training successfully increased youth congregation participation and strengthened the mosque’s role as a collaborative community space. The training of Generation Z preachers proved effective in reinforcing the khutbah's role as a holistic instrument for community development.